2000
DOI: 10.1176/appi.ps.51.6.781
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Team Leadership and Consumers' Satisfaction and Quality of Life

Abstract: Leadership seems to be an important variable for understanding a team's impact on its consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 30 publications
0
88
0
1
Order By: Relevance
“…Results have demonstrated that surgical patients are less satisfied in hospitals where surgeons reported unsatisfactory, unacceptable working conditions and reduced job satisfaction. Former studies performed by several researchers, as mentioned above, showed that satisfied medical staff has a strong influence on patients' satisfaction [77][78][79].…”
Section: Physicians Working Conditions and Job Satisfactionmentioning
confidence: 99%
“…Results have demonstrated that surgical patients are less satisfied in hospitals where surgeons reported unsatisfactory, unacceptable working conditions and reduced job satisfaction. Former studies performed by several researchers, as mentioned above, showed that satisfied medical staff has a strong influence on patients' satisfaction [77][78][79].…”
Section: Physicians Working Conditions and Job Satisfactionmentioning
confidence: 99%
“…In fact, few supervisors had but the most superficial knowledge of how their workers practiced. This ''laissez faire'' form of leadership has been found ineffective in producing high rates of client outcomes (Corrigan et al 2000). The introduction of the EBP's with their specific practice guidelines required a new set of behaviors by supervisors who had great difficulty making the transformation.…”
Section: Front-line Supervisorsmentioning
confidence: 99%
“…This intervention consisted of a cognitive-behavioural session that could limit the onset or re-define dissonant emotions (Zapf 2002;Brotheridge and Grandey 2002;Scorpiniti and Cotugno 2003). The action labeled ''Optimal strategies for work task planning and handling of the relationships with staff members'' (workshop 1b) was carried out with Group 2 members within a session inspired to Corrigan et al (1998Corrigan et al ( , 2000 and Corrigan and McCracken (1995) works.…”
Section: Materials and Proceduresmentioning
confidence: 99%